THE EFFECTIVENESS OF MOU BETWEEN COUNTRIES ON ARABIC LANGUAGE LEARNING IN UNIVERSITY - Rosada, Bintang (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Although much research has been conducted on plans involving MoU memorandums of understanding between countries, there is still very little research discussing the benefits of MoU memorandums of understanding for Arabic language learning in higher education. Therefore, this research aims to see the effectiveness of a memorandum of understanding (MOU) between Indonesia and developed countries in the economic (technological) sector on Arabic language learning in higher education. This research is included in qualitative research with a bibliographic type (reviewing literature and analyzing relevant topics). Data collection techniques use secondary data indirectly by examining related objects. Data analysis was carried out using descriptive qualitative methods in the form of written sentences and concluding the results based on previous research. The results of the research show that the effectiveness of MOU for Arabic language learning in higher education is in the form of digitalization of Arabic language learning, iconic Arabic language education majors, Arabic language as a patent curriculum, opportunities for self-development for a career on the world stage. Apart from that, the research results also show that there is an impact of the memorandum of understanding on Arabic language learning in universities in the form of a shift in interest from Arabic language learners, foreign languages becoming local content in universities, Indonesia's dependence on foreign products in facilitating Arabic language learning, misuse of technology (changes in norms and immoral acts). This research implies the importance of Arabic language educators as facilitators who continue to monitor the progress of learning in the classroom, as well as the government as a policy maker to be aware of the conveniences provided by outside parties so that they are not complacent.